2006
DOI: 10.1111/j.1600-051x.2005.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality of active‐control trials in periodontal research

Abstract: The general lack of compliance with quality criteria might place doubt on the value of these trials and may render any conclusions questionable. It is therefore important to distinguish clearly between superiority trials and equivalence trials, and to incorporate appropriate additional criteria in the design of future RCTs with active-control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Unfortunately, in dentistry 4,5,8 and other biomedical sciences, 6 many published research articles would be considered to have a low LoE. However, LoEs provide an incomplete picture since studies that have the same LoE nominally, may differ in essential methodological aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, in dentistry 4,5,8 and other biomedical sciences, 6 many published research articles would be considered to have a low LoE. However, LoEs provide an incomplete picture since studies that have the same LoE nominally, may differ in essential methodological aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic is an important advantage considering that clinical trials represent a minor portion of research articles in dentistry. 4,5,8 An additional advantage of the MINCIR scale is that it enables one to perform systematic reviews of clinical trials, cohort studies, case-control, and case series studies. 11 The MINCIR scale has been used to assess surgical studies, 6 including studies in the areas of oral and maxillofacial surgery, 8 and has demonstrated psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient statistical power with adequate sample sizes is required to detect the difference in treatment effects between groups. 25,26 Otherwise, a false-negative result (Type-II error) may occur, when there is a genuine difference in treatment effects. It may be argued that animal studies may be conducted to test the safety of pharmacological agents for their potential use in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This is often overlooked or under-reported in the oral health literature (35). This is often overlooked or under-reported in the oral health literature (35).…”
Section: Statistical Powermentioning
confidence: 99%